Fiber-reinforced paving floor for coal mine and preparation method of fiber-reinforced paving floor
By preparing fiber-reinforced paving flooring, combining antistatic and flame-retardant masterbatch and composite fibers, the problems of low strength, easy wear and deformation, and static electricity in coal mine flooring have been solved, achieving high flame retardancy and antistatic effects, and improving the service life and construction efficiency of the flooring.
Patent Information
- Application Number
- CN202511355369.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-22
- Publication Date
- 2025-10-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing coal mine floors have low strength, are easily worn and deformed, are prone to static electricity, and have poor flame retardancy, making it difficult to strike a balance between safety and durability.
The fiber-reinforced paving flooring incorporates antistatic and flame-retardant masterbatch, glass fiber filaments, and carbon fiber composites, along with antioxidants and stabilizers. During the manufacturing process, modified aluminum silicon oxide, ammonium polyphosphate, and melamine cyanurate are used to form a dense carbon layer and a stable conductive network, thereby enhancing the flooring's flame retardancy and antistatic properties.
It significantly improves the flame retardancy and antistatic properties of the flooring, enhances its mechanical properties, extends its service life, and reduces construction intensity.
Smart Images

Figure CN120842731A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of auxiliary composite materials technology in underground coal mines, and in particular to a fiber-reinforced paving floor suitable for coal mine roadways and working face areas, and its preparation method. Background Technology
[0002] The underground environment of coal mines is unique, containing flammable and explosive substances such as gas and coal dust. The roadway surfaces are often damp, with piles of gravel and crushed by equipment. The condition of the underground roadway surfaces is crucial to transportation safety and production efficiency. Therefore, coal mines have strict requirements for the performance of paving materials, such as antistatic and flame-retardant properties to avoid safety hazards, as well as sufficient mechanical strength and wear resistance to withstand long-term use.
[0003] Currently, the paving materials used in coal mines mainly include precast concrete slabs, metal sheets, and polymer flooring. Precast concrete slabs are heavy and difficult to lay, and the frequent rolling of heavy-duty vehicles in coal mines accelerates the damage to concrete pavements. Metal sheets are expensive and prone to corrosion in the humid underground environment, affecting the material's service life. Ordinary polymer polyethylene flooring is easily worn and deformed under heavy rolling, and has problems such as insufficient antistatic and flame-retardant properties, low strength, and easy wear and deformation, making it difficult to balance safety and durability.
[0004] Therefore, there is an urgent need to develop a paving floor that is suitable for the underground environment of coal mines and has excellent comprehensive performance, in order to solve the problems of low strength, easy wear and deformation, static electricity, and poor flame retardancy of existing coal mine paving floors. Summary of the Invention
[0005] The purpose of this invention is to provide a fiber-reinforced paving floor for coal mines and its preparation method, so as to solve the problems mentioned in the background art, such as low strength, easy wear and deformation, easy static electricity generation, and poor flame retardancy of existing coal mine floors.
[0006] In a first aspect, the present invention provides a fiber-reinforced paving floor for coal mines, comprising the following components in parts by weight: 55-75 parts of polyethylene, 8-18 parts of glass fiber, 8-15 parts of antistatic and flame-retardant masterbatch, 3-8 parts of carbon fiber, 2-3 parts of antioxidant, 1-3 parts of dispersant, and 1-2 parts of stabilizer.
[0007] As a preferred embodiment of the present invention, the antistatic and flame-retardant masterbatch is prepared by mixing, melting, and extruding the following components in parts by weight: 38-45 parts of polyethylene, 30-35 parts of flame retardant, 15-18 parts of antistatic agent, 2-4 parts of polyacrylic acid, and 0.5-1 parts of polyethylene 2,5-furandicarboxylate.
[0008] As a preferred embodiment of the present invention, the flame retardant is composed of modified aluminum silicon oxide, ammonium polyphosphate, and melamine cyanurate in a mass ratio of 2 to 3:1:1.
[0009] As a preferred embodiment of the present invention, the antistatic agent is composed of hexadecyltrimethylammonium bromide, polyethylene glycol, polyamide, and polyether in a mass ratio of 1-2:1-2:1:1.
[0010] As a preferred embodiment of the present invention, the antistatic flame-retardant masterbatch is prepared by the following method:
[0011] Step 1: Add polyethylene, flame retardant, antistatic agent, polyacrylic acid, and polyethylene 2,5-furandicarboxylate to a mixer with a speed of 800-900 rpm in a certain proportion, and stir for 15-20 minutes at 80-90℃ to obtain mixture A.
[0012] Step 2: Add mixture A to a twin-screw extruder with a barrel temperature of 180-190℃ via a feeder, melt, extrude, cool, and pelletize to obtain antistatic and flame-retardant masterbatch. Cooling is performed by a fan installed 80-100cm above the material conveyor belt at a speed of 3000rpm.
[0013] As a preferred embodiment of the present invention, the modified aluminum-silicon oxide is prepared by the following method: 45-50 parts by weight of aluminum oxide and 20-30 parts by weight of silicon dioxide are weighed, mixed evenly, and then placed in a calcining furnace at 500-550°C for 2.5-3 hours to obtain a calcined aluminum-silicon mixture; the calcined aluminum-silicon mixture and vinyltris(β-methoxyethoxy)silane are mixed at a mass ratio of 50-60:1 and then placed in a plasma device for treatment for 15-20 minutes to obtain the modified aluminum-silicon oxide.
[0014] As a preferred embodiment of the present invention, the polyacrylic acid has a molecular weight greater than 80,000.
[0015] As a preferred embodiment of the present invention, the polyethylene glycol has a molecular weight greater than 6000.
[0016] As a preferred embodiment of the present invention, the antioxidant is composed of 2,6-di-tert-butyl-4-methylphenol, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate octadecyl alcohol ester, and tea polyphenols in a mass ratio of 2:1:1.
[0017] As a preferred embodiment of the present invention, the dispersant is composed of zinc stearate, monostearyl phosphate, and polyethylene wax in a mass ratio of 2 to 4:1:1.
[0018] As a preferred embodiment of the present invention, the stabilizer is composed of nanocellulose and sodium carboxymethyl cellulose in a mass ratio of 1:1.
[0019] As a preferred embodiment of the present invention, the antistatic and flame-retardant masterbatch has a diameter of 2 mm and a length of 8-12 mm.
[0020] As a preferred embodiment of the present invention, the plasma device has a charge density of 950–1000 C / cm³. 3 The gas flow rate is 1.0–1.2 L / min, the pressure is 85–90 kPa, and the temperature is 60–70 °C.
[0021] As a preferred embodiment of the present invention, the particle size of the nanocellulose is 60-90 nm.
[0022] Secondly, the present invention also provides a method for preparing fiber-reinforced paving flooring for coal mines, comprising the following preparation steps:
[0023] S1. Raw material pretreatment: Cut glass fiber filaments and carbon fiber to a length of 5-10 mm, and then put them into a mixer with a speed of 1000-1200 rpm in proportion with polyethylene, antistatic and flame-retardant masterbatch, antioxidant, dispersant and stabilizer. Stir at 80-100℃ for 10-15 min to obtain mixture B.
[0024] S2. Heated extrusion: The mixture B is placed into a twin-screw extruder, and the barrel temperature is controlled at 160-190℃. After melting and mixing, it is extruded through a die to form a billet.
[0025] S3. Sheet forming: The blank is pressed into a sheet with a thickness of 10-20mm by a flattening roller, cooled to room temperature by a cooling and shaping device with a water temperature of 20-30℃, and then conveyed by a traction machine to obtain the formed sheet.
[0026] S4. Finished product processing: According to the width requirements of coal mine roadways, the shaped plates are cut to the preset length, and the edges are polished smooth to obtain fiber-reinforced paving floor for coal mines.
[0027] Compared with the prior art, the beneficial effects of the present invention are:
[0028] 1. In the preparation process of fiber-reinforced paving flooring, this invention incorporates an antistatic and flame-retardant masterbatch. The flame retardant is composed of modified aluminum silicon oxide, ammonium polyphosphate, and melamine cyanurate. The modified aluminum silicon oxide can form a dense ceramic protective layer under high temperature conditions, isolating oxygen and heat transfer, and inhibiting the combustion and dripping of the substrate. Ammonium polyphosphate (APP) can provide an acid source for the flame retardant, and decomposes upon heating to produce acidic substances such as phosphoric acid, promoting the dehydration and carbonization of the substrate to form an expanded char layer. Melamine cyanurate (MCA) serves as a gas source, decomposing under high temperature conditions to release inert gases such as NH3 to dilute flammable gases. At the same time, it synergistically enhances the expansion effect of the char layer with ammonium polyphosphate and modified aluminum silicon oxide, delaying the spread of fire. After the three are combined, through the synergistic effect of multiple mechanisms of "physical barrier + chemical expansion + gas dilution", the oxygen index of the flooring is significantly improved, thus enhancing the flame retardancy of the flooring. The rigid framework of aluminum-silicon oxide reduces molten dripping during floor combustion, lowering the risk of secondary fires. Simultaneously, the decomposition products of ammonium polyphosphate and melamine cyanurate neutralize some of the toxic gases produced during combustion, such as carbon monoxide and hydrocarbons. The nitrogen- and oxygen-containing groups in modified silanes also participate in free radical capture, further improving smoke safety during fires. Furthermore, the enhanced interfacial bonding between the modified aluminum-silicon oxide and the floor provides rigid support, increasing the floor's tensile and compressive strength. The high hardness of aluminum-silicon oxide also helps improve the floor's wear resistance and scratch resistance, extending its lifespan.
[0029] 2. In the preparation process of the antistatic and flame-retardant masterbatch, this invention incorporates antistatic agents cetyltrimethylammonium bromide (CTAB), polyethylene glycol (PEG), polyamide (PA), and polyether, upgrading the material from "single conductivity" to "highly efficient and stable conductive network." CTAB forms dense ionic conductive channels on the material surface through the directional arrangement of quaternary ammonium cations in its molecules, which can quickly release accumulated static electricity and solve the problem of "instantaneous static electricity bursts." The ether bonds and hydroxyl groups in polyethylene glycol and polyether have strong hydrophilicity and can adsorb water molecules in the environment to form a continuous water film conductive layer, compensating for the attenuation of ionic conductivity when CTAB is used alone, forming a dual channel of ionic conductivity and hygroscopic conductivity. The strong polar amide bonds in PA molecules can form a hydrogen bond network with PEG and polyether, "anchoring" the antistatic agent in the matrix to form a stable structure, thereby prolonging the antistatic effect.
[0030] 3. In the preparation process of the antistatic and flame-retardant masterbatch, this invention incorporates polyethylene 2,5-furandicarboxylate (PEF). The PEF molecular chain contains ester groups and furan rings. The polarity of the ester groups can form hydrogen bonds or dipole interactions with the hydroxyl groups of polar antistatic agents such as polyethylene glycol and the polar groups of hexadecyltrimethylammonium bromide (CTAB), reducing the aggregation of antistatic agents and improving and prolonging the antistatic effect. The hydrogen bonds between the polar matrix ester groups of PEF and the surface hydroxyl groups of flame retardants such as ammonium polyphosphate (APP) and melamine cyanurate (MCA) interact through intermolecular mechanisms. Efforts are made to improve the dispersibility of flame retardants and reduce the decline in flame retardant performance caused by agglomeration defects. The rigid structure of furan rings in the PEF molecular chain gives it high tensile and compressive strength. PEF, as a masterbatch matrix, can compensate for the decline in material mechanical properties caused by antistatic agents and flame retardants. Furthermore, PEF undergoes ester group cleavage and furan ring opening reactions during combustion, forming a certain amount of coke residue. This coke can combine with phosphate esters produced by the decomposition of ammonium polyphosphate to form a denser and tougher expanded char layer, effectively blocking heat transfer and oxygen entry, and enhancing the flame retardant effect.
[0031] 4. This invention combines glass fiber filaments with carbon fiber to improve the compressive strength and wear resistance of the flooring, enabling it to withstand the long-term pressure from mining trucks and equipment. Carbon fiber has extremely high tensile strength and elastic modulus, but is relatively brittle. Glass fiber has moderate tensile strength but superior toughness. When the two are mixed in a certain proportion, the carbon fiber bears the main load, while the glass fiber disperses stress concentration and absorbs impact energy, thereby increasing the tensile strength of the flooring. This allows it to withstand the long-term pressure from mining trucks and heavy equipment without easily cracking or deforming.
[0032] 5. Fiber-reinforced flooring is prone to mechanical property degradation due to oxidation during long-term use in high temperature, high humidity, or underground environments. This invention incorporates antioxidants 2,6-di-tert-butyl-4-methylphenol (BHT), β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and tea polyphenols during the preparation of fiber-reinforced flooring. The use of antioxidants can block oxidation reactions, maintain the interfacial bonding force of the flooring, protect the stability of the matrix and fiber interface, and extend the service life of the flooring.
[0033] 6. This invention incorporates stabilizers nanocellulose and sodium carboxymethyl cellulose during the preparation of fiber-reinforced paving flooring. The poor compatibility between the flooring's polyethylene matrix and glass or carbon fibers can lead to interfacial "debonding," affecting stress transfer. Nanocellulose, uniformly dispersed in the matrix, has abundant hydroxyl (-OH) groups on its surface that can bind to the surface treatment agent of the matrix fibers via hydrogen bonds. Sodium carboxymethyl cellulose adsorbs onto the fiber surface, forming an electrostatic barrier that prevents particle agglomeration. The -COONa and -OH polar groups in sodium carboxymethyl cellulose can form ionic bonds with the hydroxyl and amino groups on the fiber surface, further strengthening interfacial bonding and improving the flooring's compressive strength. In humid environments, the hydrophilicity of sodium carboxymethyl cellulose forms a "hydration film," reducing moisture erosion of the interface and minimizing the degradation of the material's mechanical properties in wet conditions.
[0034] 7. This invention adopts an integrated process of heated extrusion and board forming, resulting in lightweight finished flooring that can be quickly laid and replaced, reducing the intensity of underground construction and improving construction efficiency. Attached Figure Description
[0035] Figure 1 This is a flowchart illustrating the preparation process of the fiber-reinforced paving floor for coal mines according to the present invention. Detailed Implementation
[0036] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making any creative efforts shall fall within the scope of protection of the present invention.
[0037] like Figure 1 As shown, a method for preparing fiber-reinforced paving flooring for coal mines includes the following preparation steps: S1. Raw material pretreatment: Glass fiber filaments and carbon fiber are cut to a length of 5-10 mm, and then mixed with polyethylene, antistatic and flame-retardant masterbatch, antioxidant, dispersant, and stabilizer in proportion and placed in a mixer with a speed of 1000-1200 rpm. The mixture is stirred at 80-100℃ for 10-15 min to obtain mixture B; S2. Heated extrusion: Mixture B is placed in a twin-screw extruder, and the barrel temperature is controlled at 160-190℃. After melting and mixing, the mixture is extruded through a die to form a billet; S3. Sheet forming: The billet is pressed into a sheet with a thickness of 10-20 mm by a flattening roller, cooled to room temperature by a cooling and shaping device with a water temperature of 20-30℃, and then conveyed by a traction machine to obtain a shaped sheet; S4. Finished product processing: According to the width requirements of the coal mine roadway, the shaped sheet is cut to a preset length, and the edges are polished smooth to obtain fiber-reinforced paving flooring for coal mines.
[0038] All raw materials used in this invention are commercially available.
[0039] Example 1:
[0040] A fiber-reinforced paving floor for coal mines comprises the following components in parts by weight: 55 parts polyethylene, 8 parts glass fiber, 8 parts antistatic and flame-retardant masterbatch, 3 parts carbon fiber, 2 parts antioxidant (composed of BHT, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and tea polyphenols in a mass ratio of 2:1:1), 1 part dispersant (composed of zinc stearate, monostearyl phosphate, and polyethylene wax in a mass ratio of 2:1:1), and 1 part stabilizer (composed of nanocellulose with a particle size of 60-90 nm and sodium carboxymethyl cellulose in a mass ratio of 1:1).
[0041] The antistatic and flame-retardant masterbatch is prepared by the following method: (I) Preparation of modified aluminum-silicon oxide: Weigh 45 parts by weight of aluminum oxide and 20 parts by weight of silicon dioxide, mix them evenly, and place them in a calcining furnace at 500℃ for 3 hours to obtain a calcined aluminum-silicon mixture; mix the calcined aluminum-silicon mixture and vinyltris(β-methoxyethoxy)silane at a mass ratio of 50:1 and place them in a furnace with a charge density of 950C / cm³. 3 The modified aluminum silicon oxide was obtained by treating it in a plasma device with a gas flow rate of 1.0 L / min, a pressure of 85 kPa, and a temperature of 60℃ for 20 min. (II) Preparation of Mixture A: 38 parts by weight of polyethylene, 30 parts by weight of flame retardant (composed of modified aluminum silicon oxide, ammonium polyphosphate, and melamine cyanurate in a mass ratio of 2:1:1), 15 parts by weight of antistatic agent (composed of hexadecyltrimethylammonium bromide, polyethylene glycol (molecular weight greater than 6000), polyamide, and polyether in a mass ratio of 1:1:1:1), 2 parts by weight of polyacrylic acid (molecular weight greater than 80,000), and 0.5 parts by weight of polyethylene 2,5-furandicarboxylate were added to a mixer with a speed of 800 rpm and stirred at 80℃ for 20 min to obtain Mixture A. (III) Preparation of antistatic and flame-retardant masterbatch: Mixture A is fed into a twin-screw extruder with a barrel temperature of 180℃ through a feeder, melted, extruded, cooled, and pelletized to obtain antistatic and flame-retardant masterbatch with a diameter of 2mm and a length of 8-12mm. Cooling is carried out by a fan installed 80cm above the material conveyor belt with a fan speed of 3000rpm.
[0042] A method for preparing fiber-reinforced paving flooring for coal mines includes the following preparation steps:
[0043] S1. Raw material pretreatment: Cut glass fiber filaments and carbon fiber to a length of 5-10mm, and then put them into a mixer with a speed of 1000rpm in proportion with polyethylene, antistatic and flame-retardant masterbatch, antioxidant, dispersant and stabilizer, and stir at 80℃ for 15min to obtain mixture B.
[0044] S2. Heated extrusion: The mixture B is placed into a twin-screw extruder, the barrel temperature is controlled at 160℃, and after melting and mixing, it is extruded through a die to form a billet.
[0045] S3. Sheet forming: The blank is pressed into a sheet with a thickness of 20mm by a flattening roller, cooled to room temperature by a cooling and shaping device with a water temperature of 20-30℃, and then conveyed by a traction machine to obtain the formed sheet.
[0046] S4. Finished product processing: According to the width requirements of coal mine roadways, the shaped plates are cut to the preset length, and the edges are polished smooth to obtain fiber-reinforced paving floor for coal mines.
[0047] Example 2:
[0048] A fiber-reinforced paving floor for coal mines comprises the following components in parts by weight: 75 parts polyethylene, 18 parts glass fiber, 15 parts antistatic and flame-retardant masterbatch, 8 parts carbon fiber, 3 parts antioxidant (composed of BHT, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and tea polyphenols in a mass ratio of 2:1:1), 3 parts dispersant (composed of zinc stearate, monostearyl phosphate, and polyethylene wax in a mass ratio of 4:1:1), and 2 parts stabilizer (composed of nanocellulose with a particle size of 60-90 nm and sodium carboxymethyl cellulose in a mass ratio of 1:1).
[0049] The antistatic and flame-retardant masterbatch is prepared by the following method: (I) Preparation of modified aluminum-silicon oxide: Weigh 50 parts by weight of alumina and 30 parts by weight of silicon dioxide, mix them evenly, and place them in a calcining furnace at 550℃ for 2.5h to obtain a calcined aluminum-silicon mixture; mix the calcined aluminum-silicon mixture and vinyltris(β-methoxyethoxy)silane at a mass ratio of 60:1 and place them in a furnace with a charge density of 1000C / cm³. 3The modified aluminum silicon oxide was obtained by treating it in a plasma device with a gas flow rate of 1.2 L / min, a pressure of 90 kPa, and a temperature of 70℃ for 15 min. (II) Preparation of Mixture A: 45 parts by weight of polyethylene, 35 parts by weight of flame retardant (composed of modified aluminum silicon oxide, ammonium polyphosphate, and melamine cyanurate in a mass ratio of 3:1:1), 4 parts by weight of antistatic agent (composed of hexadecyltrimethylammonium bromide, polyethylene glycol (molecular weight greater than 6000), polyamide, and polyether in a mass ratio of 2:2:1:1), 4 parts by weight of polyacrylic acid (molecular weight greater than 80,000), and 1 part by weight of polyethylene 2,5-furandicarboxylate were added to a mixer with a speed of 900 rpm and stirred at 90℃ for 15 min to obtain Mixture A. (III) Preparation of antistatic and flame-retardant masterbatch: Mixture A is fed into a twin-screw extruder with a barrel temperature of 190℃ through a feeder, melted, extruded, cooled, and pelletized to obtain antistatic and flame-retardant masterbatch with a diameter of 2mm and a length of 8-12mm. Cooling is carried out by a fan installed 80cm above the material conveyor belt with a fan speed of 3000rpm.
[0050] A method for preparing fiber-reinforced paving flooring for coal mines includes the following preparation steps:
[0051] S1. Raw material pretreatment: Cut glass fiber filaments and carbon fiber to a length of 5-10 mm, and then put them into a mixer with a speed of 1200 rpm in proportion with polyethylene, antistatic and flame-retardant masterbatch, antioxidant, dispersant and stabilizer. Stir at 100℃ for 10 min to obtain mixture B.
[0052] S2. Heated extrusion: The mixture B is placed into a twin-screw extruder, the barrel temperature is controlled at 190℃, and after melting and mixing, it is extruded through a die to form a billet.
[0053] S3. Sheet forming: The blank is pressed into a sheet with a thickness of 10mm by a flattening roller, cooled to room temperature by a cooling and shaping device with a water temperature of 20-30℃, and then conveyed by a traction machine to obtain the formed sheet.
[0054] S4. Finished product processing: According to the width requirements of coal mine roadways, the shaped plates are cut to the preset length, and the edges are polished smooth to obtain fiber-reinforced paving floor for coal mines.
[0055] Example 3:
[0056] A fiber-reinforced paving floor for coal mines comprises the following components in parts by weight: 70 parts polyethylene, 10 parts glass fiber, 12 parts antistatic and flame-retardant masterbatch, 5 parts carbon fiber, 2 parts antioxidant (composed of BHT, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and tea polyphenols in a mass ratio of 2:1:1), 2 parts dispersant (composed of zinc stearate, monostearyl phosphate, and polyethylene wax in a mass ratio of 3:1:1), and 1.5 parts stabilizer (composed of nanocellulose with a particle size of 60-90 nm and sodium carboxymethyl cellulose in a mass ratio of 1:1).
[0057] The antistatic and flame-retardant masterbatch is prepared by the following method: (I) Preparation of modified aluminum-silicon oxide: Weigh 48 parts by weight of alumina and 25 parts by weight of silicon dioxide, mix them evenly, and place them in a calcining furnace at 520℃ for 3 hours to obtain a calcined aluminum-silicon mixture; mix the calcined aluminum-silicon mixture and vinyltris(β-methoxyethoxy)silane at a mass ratio of 55:1 and place them in a furnace with a charge density of 1000C / cm³. 3 The modified aluminum silicon oxide was obtained by treating it in a plasma device with a gas flow rate of 1.1 L / min, a pressure of 90 kPa, and a temperature of 65℃ for 18 min. (II) Preparation of Mixture A: 40 parts by weight of polyethylene, 32 parts by weight of flame retardant (composed of modified aluminum silicon oxide, ammonium polyphosphate, and melamine cyanurate in a mass ratio of 2:1:1), 16 parts by weight of antistatic agent (composed of hexadecyltrimethylammonium bromide, polyethylene glycol (molecular weight greater than 6000), polyamide, and polyether in a mass ratio of 1:2:1:1), 3 parts by weight of polyacrylic acid (molecular weight greater than 80,000), and 0.8 parts by weight of polyethylene 2,5-furandicarboxylate were added to a mixer with a speed of 850 rpm and stirred at 85℃ for 18 min to obtain mixture A. (III) Preparation of antistatic and flame-retardant masterbatch: Mixture A is fed into a twin-screw extruder with a barrel temperature of 185℃ by a feeder, melted, extruded, cooled and pelletized to obtain antistatic and flame-retardant masterbatch with a diameter of 2mm and a length of 8-12mm. Cooling is carried out by a fan installed 80cm above the material conveyor belt with a fan speed of 3000rpm.
[0058] A method for preparing fiber-reinforced paving flooring for coal mines includes the following preparation steps:
[0059] S1. Raw material pretreatment: Cut glass fiber filaments and carbon fiber to a length of 5-10 mm, and then put them into a mixer with a speed of 1100 rpm in proportion with polyethylene, antistatic and flame-retardant masterbatch, antioxidant, dispersant and stabilizer. Stir at 90℃ for 12 min to obtain mixture B.
[0060] S2. Heated extrusion: The mixture B is placed into a twin-screw extruder, the barrel temperature is controlled at 180℃, and after melting and mixing, it is extruded through a die to form a billet.
[0061] S3. Sheet forming: The blank is pressed into a sheet with a thickness of 15mm by a flattening roller, cooled to room temperature by a cooling and shaping device with a water temperature of 20-30℃, and then conveyed by a traction machine to obtain the formed sheet.
[0062] S4. Finished product processing: According to the width requirements of coal mine roadways, the shaped plates are cut to the preset length, and the edges are polished smooth to obtain fiber-reinforced paving floor for coal mines.
[0063] Comparative Example 1:
[0064] The difference from Example 1 is that the modified aluminum silicon oxide is removed.
[0065] Comparative Example 2:
[0066] The difference from Example 1 is that the flame retardant is removed.
[0067] Comparative Example 3:
[0068] The difference from Example 1 is that the antistatic agent is removed.
[0069] Comparative Example 4:
[0070] The difference from Example 1 is that polyethylene 2,5-furandicarboxylate is removed.
[0071] Comparative Example 5:
[0072] The difference from Example 1 is that nanocellulose is removed.
[0073] Comparative Example 6:
[0074] The difference from Example 1 is that sodium carboxymethyl cellulose is removed.
[0075] Comparative Example 7:
[0076] The difference from Example 1 is that the antioxidant is removed.
[0077] Comparative Example 8:
[0078] The difference from Example 1 is that the glass fiber filaments are removed.
[0079] Comparative Example 9:
[0080] The difference from Example 1 is that the carbon fiber is removed.
[0081] The fiber-reinforced flooring for coal mines prepared in Examples 1, 2, 3 and Comparative Examples 1, 2, 3, 4, 5, 6, 7, 8, and 9 were subjected to performance tests.
[0082] The surface resistance of the floor was tested according to GB / T 36340-2018 "General Specification for Antistatic Raised Floors"; the oxygen index of the floor was tested according to GB / T2406.2-2009 "Determination of Combustion Behavior by Oxygen Index Method for Plastics - Part 2: Room Temperature Test"; the compressive strength of the floor was tested using a NAN-KY160 compressive strength tester; the tensile strength of the floor was tested using a B618-S tensile testing machine; and the abrasion resistance of the floor was tested according to GB / T 4085-2015 "Semi-rigid Polyvinyl Chloride Block Flooring". The results are shown in Table 1.
[0083] Table 1: Performance Test Table for Fiber Reinforced Flooring for Coal Mines
[0084]
[0085] As shown in Table 1, the fiber-reinforced flooring for coal mines prepared in Examples 1, 2, and 3 has lower surface resistivity, higher oxygen index, higher compressive strength, higher tensile strength, and better wear resistance compared to Comparative Examples 1, 2, 3, 4, 5, 6, 8, and 9.
[0086] Surface resistivity reflects the conductivity of the floor's surface layer. Low surface resistivity effectively prevents static electricity buildup, avoiding the risk of electric shock. The oxygen index of polymer materials measures their flame retardancy. A higher oxygen index means a higher oxygen concentration is required for combustion, making it difficult for the material to sustain combustion in air, exhibiting good flame retardancy. Greater compressive strength means the floor can better withstand the pressure of mine cars and equipment in coal mines. Tensile strength reflects the floor's resistance to fracture; greater tensile strength means greater resistance to breakage. Abrasion resistance is the volume loss of the floor after 100 revolutions of wear resistance. A higher abrasion resistance index indicates greater volume loss and poorer abrasion resistance.
[0087] Modified aluminum silicate oxide synergistically enhances the char layer expansion effect, delaying the spread of fire. When combined with ammonium polyphosphate and melamine cyanurate, modified aluminum silicate oxide, through a multi-mechanism synergistic effect of "physical barrier + chemical expansion + gas dilution," increases the oxygen index of the flooring and improves its flame retardancy. Simultaneously, the modified aluminum silicate oxide exhibits enhanced interfacial bonding with the flooring, providing rigid support and improving the flooring's tensile and compressive strength. Furthermore, the high hardness of aluminum silicate oxide helps improve the flooring's abrasion resistance. The addition of antistatic agents such as hexadecyltrimethylammonium bromide (CTAB), polyethylene glycol (PEG), polyamide (PA), and polyether enhances the flooring's antistatic effect and prevents static electricity accumulation. 2,5-Polyethylene 2,5-furandicarboxylate (PEF) reduces the aggregation of antistatic agents, improving and prolonging the antistatic effect. The rigid structure of the furan ring in the PEF molecular chain gives it high tensile and compressive strength. Furthermore, during combustion, PEF undergoes ester group breakage and furan ring-opening reactions, forming a certain amount of char residue. This char can combine with phosphate esters produced by the decomposition of ammonium polyphosphate to form a denser, tougher expanded char layer, effectively blocking heat transfer and oxygen entry, thus enhancing the flame-retardant effect. The composite of glass fiber and carbon fiber improves the compressive strength and abrasion resistance of the flooring, enabling it to withstand the pressure of mining vehicles and equipment for extended periods. Nanocellulose and sodium carboxymethyl cellulose further strengthen the interfacial bonding, improving the antistatic effect, flame-retardant properties, and compressive strength of the flooring.
[0088] The fiber-reinforced flooring for coal mines prepared in Example 1 and Comparative Example 7 were placed in coal mines under the same conditions for 6 months and 12 months. The surface resistance, oxygen index and compressive strength of the flooring were then tested, as shown in Table 2.
[0089] Table 2: Performance Variation of Fiber Reinforced Flooring for Coal Mines
[0090]
[0091] The initial surface resistivity, oxygen index, and compressive strength of the fiber-reinforced flooring for coal mines prepared in Example 1 were 6 × 10⁻⁶. 7 The initial surface resistivity, oxygen index, and compressive strength of the fiber-reinforced flooring for coal mines prepared in Comparative Example 7 were 7 × 10⁻⁶ MPa, 34.6%, and 35.8 MPa, respectively. 7 Ω, 33.4%, and 33.6 MPa. As the floor is placed in the coal mine for an extended period, the surface resistivity of the floor increases, while the oxygen index and compressive strength decrease.
[0092] Antioxidants such as 2,6-di-tert-butyl-4-methylphenol, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and tea polyphenols can block oxidation reactions, maintain the interfacial bonding of the flooring, protect the stability of the matrix and fiber interface, and extend the service life of the flooring.
[0093] The densities of the fiber-reinforced flooring for coal mines prepared in Examples 1, 2, and 3 were determined to be 1.2 g / cm³ according to GB / T 1463-2005 "Test Methods for Density and Relative Density of Fiber-Reinforced Plastics". 3 1.1g / cm 3 and 1.1 g / cm 3 The flooring prepared in this embodiment is lightweight, allowing for quick installation and replacement, thus reducing the intensity of underground construction.
[0094] In summary, the fiber-reinforced flooring for coal mines produced by this invention has high strength, is not easily worn or deformed, has good antistatic and flame-retardant properties, and is lightweight, allowing for quick installation and replacement, thus reducing the intensity of underground coal mine construction.
[0095] The above are merely specific embodiments of the present invention, but the technical features of the present invention are not limited thereto. Any simple changes, equivalent substitutions, or modifications made based on the present invention to solve essentially the same technical problems and achieve essentially the same technical effects are all covered within the protection scope of the present invention.
Claims
1. A fiber-reinforced paving floor for coal mines, characterized in that, It includes the following components in parts by weight: 55-75 parts polyethylene, 8-18 parts glass fiber, 8-15 parts antistatic and flame-retardant masterbatch, 3-8 parts carbon fiber, 2-3 parts antioxidant, 1-3 parts dispersant, and 1-2 parts stabilizer. The antistatic and flame-retardant masterbatch is prepared by mixing, melting, and extruding the following components in parts by weight: 38-45 parts polyethylene, 30-35 parts flame retardant, 15-18 parts antistatic agent, 2-4 parts polyacrylic acid, and 0.5-1 parts polyethylene 2,5-furandicarboxylate. The flame retardant is composed of modified aluminum silicon oxide, ammonium polyphosphate, and melamine cyanurate in a mass ratio of 2-3:1:1; The antistatic agent is composed of hexadecyltrimethylammonium bromide, polyethylene glycol, polyamide, and polyether in a mass ratio of 1-2:1-2:1:
1.
2. The fiber-reinforced paving floor for coal mines according to claim 1, characterized in that, The antistatic and flame-retardant masterbatch is prepared by the following method: Step 1: Add polyethylene, flame retardant, antistatic agent, polyacrylic acid, and polyethylene 2,5-furandicarboxylate into a mixer with a speed of 800-900 rpm in a certain proportion, and stir for 15-20 minutes at 80-90℃ to obtain mixture A; Step 2: Add mixture A to a twin-screw extruder with a barrel temperature of 180-190℃ via a feeder, melt, extrude, cool, and pelletize to obtain antistatic and flame-retardant masterbatch.
3. The fiber-reinforced paving floor for coal mines according to claim 1, characterized in that, The modified aluminum-silicon oxide is prepared by the following method: 45-50 parts by weight of aluminum oxide and 20-30 parts by weight of silicon dioxide are weighed, mixed evenly, and placed in a calcining furnace at 500-550°C for 2.5-3 hours to obtain a calcined aluminum-silicon mixture; the calcined aluminum-silicon mixture and vinyltris(β-methoxyethoxy)silane are mixed at a mass ratio of 50-60:1 and then placed in a plasma device for treatment for 15-20 minutes to obtain the modified aluminum-silicon oxide.
4. The fiber-reinforced paving floor for coal mines according to claim 1, characterized in that, The molecular weight of the polyacrylic acid is greater than 80,000; the molecular weight of the polyethylene glycol is greater than 6,000.
5. The fiber-reinforced paving floor for coal mines according to claim 1, characterized in that: The antioxidant is composed of 2,6-di-tert-butyl-4-methylphenol, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate octadecyl alcohol ester, and tea polyphenols in a mass ratio of 2:1:
1. The dispersant is composed of zinc stearate, monostearyl phosphate, and polyethylene wax in a mass ratio of 2 to 4:1:
1. The stabilizer is composed of nanocellulose and sodium carboxymethyl cellulose in a mass ratio of 1:
1.
6. The fiber-reinforced paving floor for coal mines according to claim 2, characterized in that, The cooling is achieved by using a fan installed 80-100cm above the material conveyor belt, with the fan speed at 3000rpm.
7. The fiber-reinforced paving floor for coal mines according to claim 2, characterized in that, The antistatic and flame-retardant masterbatch has a diameter of 2 mm and a length of 8–12 mm.
8. The fiber-reinforced paving floor for coal mines according to claim 3, characterized in that, The plasma device has a charge density of 950–1000 C / cm³. 3 The gas flow rate is 1.0–1.2 L / min, the pressure is 85–90 kPa, and the temperature is 60–70 °C.
9. A fiber-reinforced paving floor for coal mines according to claim 5, characterized in that, The nanocellulose has a particle size of 60–90 nm.
10. A method for preparing fiber-reinforced paving flooring for coal mines according to any one of claims 1 to 9, characterized in that, The preparation steps include the following: S1. Raw material pretreatment: Cut glass fiber filaments and carbon fiber to a length of 5-10 mm, and then put them into a mixer with a speed of 1000-1200 rpm in proportion with polyethylene, antistatic and flame-retardant masterbatch, antioxidant, dispersant and stabilizer, and stir at 80-100℃ for 10-15 min to obtain mixture B; S2. Heated extrusion: The mixture B is placed into a twin-screw extruder, and the barrel temperature is controlled at 160-190℃. After melting and mixing, it is extruded through a die to form a billet. S3. Sheet forming: The blank is pressed into a sheet with a thickness of 10-20mm by a flattening roller, cooled to room temperature by a cooling and shaping device with a water temperature of 20-30℃, and then conveyed by a traction machine to obtain the formed sheet; S4. Finished product processing: According to the width requirements of coal mine roadways, the shaped plates are cut to the preset length, and the edges are polished smooth to obtain fiber-reinforced paving floor for coal mines.
Citation Information
Patent Citations
Polyethylene composition, polyethylene material, polyethylene plate, preparation method of polyethylene plate and application of polyethylene plate in mine paving
CN116041817A
Preparation method of high-performance high-density polyethylene composite material
CN119350743A
High-weather-resistance composite modified road hot-melt coating and low-temperature preparation process thereof
CN120248693A
Flame-retardant antistatic HDPE (high-density polyethylene) master batch as well as preparation method and application thereof
CN120464121A